Transcriptome Analysis of Glycerin Regulating Reuterin Production of Lactobacillus reuteri - Jingjing Wang; Qiang Yin; Han Bai; Wei Wang; Yajun Chen; Minghui Zhou; Ran Zhang; Guoao Ding; Zhongdong Xu; Yan Zhang (Microorganisms, 2023)
Reuterin can be produced from glycerol dehydration catalyzed by glycerol dehydratase (GDHt) in Lactobacillus reuteri and has broad application prospects in industry, agriculture, food, and other fields as it is active against prokaryotic and eukaryotic organisms and is resistant to proteases and lipases. However, high concentrations of glycerin inhibit reuterin production, and the mechanism behind this phenomenon is not clear. To elucidate the inhibitory mechanism of glycerol on reuterin synthesis in L. reuteri and provide reference data for constructing an L. reuteri culture system for highly effective 3-hydroxypropionaldehyde synthesis, we used transcriptome-sequencing technology to compare the morphologies and transcriptomes of L. reuteri cultured in a medium with or without 600 mM of glycerol. Our results showed that after the addition of 600 mM of glycerol to the culture medium and incubation for 10 h at 37 °C, the culture medium of L. reuteri LR301 exhibited the best bacteriostatic effect, and the morphology of L. reuteri cells had significantly changed. The addition of 600 mM of glycerol to the culture medium significantly altered the transcriptome and significantly downregulated the transcription of genes involved in glycol metabolism, such as gldA, dhaT, glpK, plsX, and plsY, but significantly upregulated the transcription of genes related to D-glucose synthesis.